ANALISIS PENDAPATAN PETANI KARET DI KECAMATAN ANJUNGAN KABUPATEN MEMPAWAH - B21109006, Feryandi (Jurnal Pembangunan dan Pemerataan, 2017)
This study aims to do, "ANALYSIS OF INCOME FARMER RUBBER IN DISTRICTS ANJUNGAN MEMPAWAH REGENCY" is basically to determine the income of rubber farmers and constraints faced by rubber farmers and how the government's efforts in welfare for rubber farmers in Sub Anjongan Mempawah Regency. The methodology used in this research is using qualitative descriptive method, this study illustrates the existing problems in the field and analyzed in accordance with the data and facts. The analytical tool used include gross revenue (TR), Net Income (Ï€), Total cost (TC). The research concludes that the income of rubber farmers from 100 respondents with a land area of 125 hectares of rubber plantation in District Anjungan Mempawah Regency is equal Rp.194.850.000 and subtract the cost of the total expenditure of Rp.62.630.000 Rp.132.220.000, so when income per person averaged rubber farmers Mempawah District Subdistrict Platform for Rp.1.322.200 / month. Keywords: Rubber Farmer, Gross revenue (TR), Net Income (Ï€), Total cost (TC).